Experimental and DFT Studies of Au Deposition Over WO3/g-C3N4 Z-Scheme Heterojunction - Humayun, Muhammad; Ullah, Habib; Cao, Junhao; Pi, Wenbo; Yuan, Yang; Ali, Sher; Tahir, Asif Ali; Yue, Pang; Khan, Abbas; Zheng, Zhiping; Fu, Qiuyun; Luo, Wei (Nano-Micro Letters, 2019)
A typical Z-scheme system is composed of two photocatalysts which generate two sets of charge carriers and split water into H2 and O2 at different locations. Scientists are struggling to enhance the efficiencies of these systems by maximizing their light absorption, engineering more stable redox couples, and discovering new O2 and H2 evolutions co-catalysts. In this work, Au decorated WO3/g-C3N4 Z-scheme nanocomposites are fabricated via wet-chemical and photo-deposition methods. The nanocomposites are utilized in photocatalysis for H2 production and 2,4-dichlorophenol (2,4-DCP) degradation. It is investigated that the optimized 4Au/6% WO3/CN nanocomposite is highly efficient for production of 69.9 and 307.3 µmol h−1 g−1 H2 gas, respectively, under visible-light (λ > 420 nm) and UV–visible illumination. Further, the fabricated 4Au/6% WO3/CN nanocomposite is significant (i.e., 100% degradation in 2 h) for 2,4-DCP degradation under visible light and highly stable in photocatalysis. A significant 4.17% quantum efficiency is recorded for H2 production at wavelength 420 nm. This enhanced performance is attributed to the improved charge separation and the surface plasmon resonance effect of Au nanoparticles. Solid-state density functional theory simulations are performed to countercheck and validate our experimental data. Positive surface formation energy, high charge transfer, and strong non-bonding interaction via electrostatic forces confirm the stability of 4Au/6% WO3/CN interface. Highlights 1 Experimental and density functional theory studies were performed for Au decorated WO3/g-C3N4 Z-scheme heterojunction. 2 The amount optimized 4Au/6WO3/CN composite exhibited high performance for H2 evolution and 2,4-DCP degradation due to the improved charge separation in WO3/g-C3N4 composite and the surface plasmon resonance ct of Au.